2021
DOI: 10.1021/acs.jpcb.1c00592
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Membrane Permeability of Double-Chained 1,3-Dialkylimidazolium Cations in Ionic Liquids

Abstract: We have evaluated ionic liquids based on double-chained 1-alkyl-3-octylimidazolium cations ([C n C8IM]+, n = 2, 4, 6, 8, 10, 12) for their cytotoxicity toward various cell lines. The toxicity of ionic liquids was correlated to their ability to partition into and permeabilize phosphocholine (POPC)- or phosphoglycerol (POPG)-based large unilamellar vesicles. Membrane partitioning of ionic liquids was assessed using the ζ-potential measurements, and membrane permeability was determined using fluorescence-based dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…ILs are ionic compounds composed by an organic cation and either an organic or inorganic anion, which possess a variety of intriguing characteristics such as being liquid around room temperature. , An initial set of biological studies have stimulated a more recent series of chemical-physical investigations on the interaction between ILs and biomolecules. , Among those studies, a special focus has been dedicated to the investigation of IL-biomembrane interactions. , In this context, neutron reflectivity and molecular dynamics (MD) simulations have shown the microscopic mechanism of insertion of imidazolium and choline IL-cations into phospholipid bilayers which, at equilibrium, results in about three to seven IL-cations for every ten lipids absorbed in the lipid phase. The MD simulations, moreover, have also shown that the presence of IL-cations in the lipid region does alter the bilayer bending modulus.…”
Section: Introductionmentioning
confidence: 99%
“…ILs are ionic compounds composed by an organic cation and either an organic or inorganic anion, which possess a variety of intriguing characteristics such as being liquid around room temperature. , An initial set of biological studies have stimulated a more recent series of chemical-physical investigations on the interaction between ILs and biomolecules. , Among those studies, a special focus has been dedicated to the investigation of IL-biomembrane interactions. , In this context, neutron reflectivity and molecular dynamics (MD) simulations have shown the microscopic mechanism of insertion of imidazolium and choline IL-cations into phospholipid bilayers which, at equilibrium, results in about three to seven IL-cations for every ten lipids absorbed in the lipid phase. The MD simulations, moreover, have also shown that the presence of IL-cations in the lipid region does alter the bilayer bending modulus.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main problem of these chemicals is their toxicity. There are some studies about their toxicity, biodegradability, and ecotoxicity, but there is not yet enough evidence, and more studies are needed in order to ensure the safety of ILs for the environment and health [13][14][15][16][17].…”
Section: Deep Eutectic Solvents (Dess)mentioning
confidence: 99%
“…Cytotoxicity, however, requires affinity. This has motivated, in turn, a series of investigations aimed at understanding the chemical–physical origins of these interactions, to be then exploited in applications. , In this context, several biochemical and chemical physics studies on the effects of ILs on proteins, biomembranes, saccharides, and cells have been carried out in the last decade. , It has been shown, for example, that ILs are able to stabilize proteins, , to either favor or inhibit the formation of amyloids, , to disrupt biomembranes, and to kill bacteria and cancer cells at doses that are not lethal to healthy cells. , Among all of these studies, one of the major focuses has been devoted to the investigation of the interactions between ILs and model biomembranes, mimicked by lipid bilayers. , It has been shown, in this context, that IL cations, dispersed at low doses at the water–bilayer interface, diffuse into the lipid region of the bilayer, , causing variations in the lipid dynamics , and bilayer mechanoelasticity. ,,, …”
Section: Introductionmentioning
confidence: 99%